Radiographic Features and Clinical Factor for Preoperative Prediction in the Bulging Duodenal Papilla With Malignancy - Wang, Xiao-Jie; Ke, Jun-Li; Xu, Jian-Xia; Zhou, Jia-Ping; Lu, Yuan-Fei; Zhou, Qiao-Mei; Shi, Dan; Yu, Ri-Sheng (Frontiers in Oncology, 2021)
Background To investigate characteristic clinical and imaging features and establish a scoring system for preoperative prediction of malignancy in the bulging duodenal papilla. Methods A total of 147 patients with bulging duodenal papilla (Benign enlargement n=67; malignant enlargement n=80) from our hospital between 2010 and 2020 were retrospectively analyzed. We investigated meaningful clinical and CT imaging features and established the score model through logistic regression and weighted. The calibration test, the ROC, AUC and cut-off points were performed in score model. The model was also divided into three score ranges for convenient clinical evaluation. Results Three clinical and CT imaging features were finally included in the score model including direct bilirubin (DBil) increase >7 umol/L (3 points), pancreatic duct (PD) dilation >5mm (2 points) and irregular shape (2 points). The AUCs of the primary predictive model and score model were 0.896 (95%CI 0.835-0.940) and 0.896 (95%CI 0.835-0.940), respectively. This scoring system presented with a sensitivity of 78.8% and a spectivity of 88.1% when using 2.5 points as cutoff value. 3 score ranges were also proposed for convenient clinical use as follows: 0-2 points; 3-4 points; 5-7 points. The number of patients with malignant duodenal papillary enlargement increased with the increasing scores. Conclusions We proposed a convenient scoring system to preoperative predict malignancy in the bulging duodenal papilla.